Strigolactone alleviates the salinity-alkalinity stress of Malus hupehensis seedlings - Changqing Ma; Changqing Ma; Chuanjie Bian; Chuanjie Bian; Wenjie Liu; Wenjie Liu; Zhijuan Sun; Xiangli Xi; Xiangli Xi; Dianming Guo; Dianming Guo; Xiaoli Liu; et al. (Frontiers in Plant Science, 2022)
Salinity-alkalinity stress can remarkably affect the growth and yield of apple. Strigolactone (SL) is a class of carotenoid-derived compounds that functions in stress tolerance. However, the effects and mechanism of exogenous SL on the salinity-alkalinity tolerance of apple seedlings remain unclear. Here, we assessed the effect of SL on the salinity-alkalinity stress response of Malus hupehensis seedlings. Results showed that treatment with 100 μM exogenous SL analog (GR24) could effectively alleviate salinity-alkalinity stress with higher chlorophyll content and photosynthetic rate than the apple seedlings without GR24 treatment. The mechanism was also explored: First, exogenous GR24 regulated the expression of Na+/K+ transporter genes and decreased the ratio of Na+/K+ in the cytoplasm to maintain ion homeostasis. Second, exogenous GR24 increased the enzyme activities of superoxide, peroxidase and catalase, thereby eliminating reactive oxygen species production. Third, exogenous GR24 alleviated the high pH stress by regulating the expression of H+-ATPase genes and inducing the production of organic acid. Last, exogenous GR24 application increased endogenous acetic acid, abscisic acid, zeatin riboside, and GA3 contents for co-responding to salinity-alkalinity stress indirectly. This study will provide important theoretical basis for analyzing the mechanism of exogenous GR24 in improving salinity-alkalinity tolerance of apple.